A Biomimetic, Biocompatible OECT Sensor for the Real‐Time Measurement of Concentration and Saturation of Ions in Plant Sap. (12th June 2022) - Gentile, Francesco; Vurro, Filippo; Janni, Michela; Manfredi, Riccardo; Cellini, Francesco; Petrozza, Angelo; Zappettini, Andrea; Coppedè, Nicola
Abstract: Currently, the transport of ions and nutrients in the plant stem is determined by destructive techniques or by radiolabeled compounds. Here, materials science and mathematical modeling have been combined to develop a sensor device that can monitor in real time and simultaneously the concentration of ions and the saturation in the plant's xylem. The device, based on the technology of organic electrochemical transistors, is biomimetic, biocompatible, low‐cost, and minimally invasive. The mathematical model decodes the sensor's response and decouples the effects of concentration and saturation over time. In this work, this scheme is demonstrated by monitoring the condition of tomato plants subjected to vapor pressure deficit for 16 d, and to drought and salt stress for up to 25 d. Results of the work have the potential to impact on the analysis of plant's physiology, improve water use efficiency in small and large‐scale agriculture, and maximize yield with a minimum amount of fertilizer/nutrients. Abstract : A biomimetic, biocompatible, low‐cost and minimally invasive sensor device is demonstrated that is capable of monitoring in real time and simultaneously the concentration of ions and the saturation in plants. The device uses organic electrochemical transistors to accomplish the continuous measure of the sap in a non‐destructive fashion. Then, a mathematical model decouples the effects of concentration and saturation over time.